Assessment of the Relationship Between Facial and Dental Midlines with Anatomical Landmarks of the Face and Oral Cavity - Abolfazl Farahani; Karim Jafari; Ali Hemmati; Abbas Naghizadeh; Rahman Nemati; Mohammad Hossein Farahani (Galenos Yayinevi, 2019)
Objective:The purpose of the present study was to determine the facial anatomical landmarks, in order of accuracy, closest to the midline of the face, as well as oral cavity midline, and to specify which intraoral anatomical landmarks are closer to the dental midline.Methods:Three commonly used anatomical landmarks including nasion, nose, and philtrum tips were marked clinically in 108 subjects. A frontal full-face digital image was used for midline analysis in accordance with the esthetic frame. Deviations from the facial and oral midlines were measured for the three clinical landmarks. Dental midline was considered as the fourth landmark. Alginate impressions were taken, and casts were analyzed under standardized conditions. The labial frenum and incisive papilla were marked. Cast images were taken and analyzed.Results:Data showed difference between the mean ratios of the selected anatomical landmarks and the facial and oral midlines (p≤0/05). The anatomical landmark hierarchies, in proximity to the facial midline, are commissural midlines, nasion, philtrum tip, nose tip, and dental midline, respectively. The anatomical landmark hierarchies, in proximity to the commissural midline, include dental midline, philtrum tip, nose tip, and nasion. The labial frenum was less deviated from the dental midline than the incisive papilla.Conclusion:With respect to shortcomings, the results showed that all of the anatomical landmarks were deviated from the facial and oral midlines. The order of proximity of the anatomical landmarks to the facial midline was as follows: commissural midline, nasion, philtrum, and dental midline.